The quasi-Islamic foundations of social movements in Rumelia up to the mid-sixteenth century - Hauziński, Jerzy (Balcanica Posnaniensia. Acta et studia, 2011)
The article is devoted to the quasi-Islamic and Sufi foundations of social movements developing in Rumelia from the fifteenth to the mid-sixteenth century. The author analyzes the role of mystical trends within Islam, especially Sufism, in inspiring social rebellions and opposition movements against the Ottoman state. The aim of the article is to demonstrate the relationship between heterodox religious trends and social uprisings in the Ottoman Empire. The author employs a historical-comparative method and an analysis of Ottoman sources and literature concerning Sufism. Particular attention is devoted to the activity of Sheikh Bedreddin, who combined mystical ideas with a social and political program in opposition to Sultan Mehmed I. The study demonstrates that these movements possessed a syncretic character, combining elements of Shiite messianism, Sufism, and social populism. The results of the analysis indicate that heterodox religious movements played an important role in shaping the social and political landscape of Rumelia and influenced relations between the Ottoman state and the Balkan population.